Biomarker Responses of Spanish Moss Tillandsia usneoides to Atmospheric Hg and Hormesis in This Species - Sun, Xingyue; Li, Peng; Zheng, Guiling (Frontiers in Plant Science, 2021)
Hg is an environmental pollutant with severe biotoxicity. Epiphytic Tillandsia species, especially Spanish moss T. usneoides, are widely used as the bioindicator of Hg pollution. However, the effects of different Hg concentrations on Tillandsia have been rarely studied and the occurrence of hormesis in Tillandsia species has not been determined. In this study, T. usneoides was subjected to stress induced by 15 concentrations of gaseous Hg ranging from 0 to 1.8 μg·m-3 through a misting system and then Hg content and eight common biomarkers in leaves were measured. The results showed that leaf Hg content significantly increased with Hg concentration, showing a linear relationship. However, there were no obvious mortality symptoms, indicating that T. usneoides showed strong resistance to Hg. Conversely, there were no simple linear relationships between changes in various biomarkers following Hg treatment of T. usneoides and Hg concentration. With increasing Hg concentration, malondialdehyde (MDA) content did not change significantly, superoxide anion radical content decreased gradually, superoxide dismutase (SOD) content decreased to the bottom and then bounced back, electrical conductivity increased, and glutathione (GSH) and metallothionein (MT) content increased to the peak and then dropped. The coefficient of determination of the dose-effect curves between SOD, GSH and MT contents and Hg concentration was high, and the dose-effect relationship varied with hormesis. The present study is first to confirm hormesis induced by heavy metal pollution in Tillandsia species.